Understanding patterns of disruption : lessons learned from the cloud, machine learning, and more - McCallum, Q. Ethan; Gleason, Ken (O'Reilly Media, 2018)
From startups to established market leaders, many companies today are taking advantage of disruptive forces to produce new products, become more efficient, or demolish barriers to entry. The web is a good example of a disruptive force, but subtler forms of disruption such as new tools or a fresh take on old ideas can also give your business a much needed boost. In this ebook, Q. McCallum and Ken Gleason take you through several disruption examples and provide a framework to help you spot a disruption opportunity in the wild. Whether it's applying an existing technology in a new way, creating a new business model or market segment, or launching a value network that invites other companies to provide resources or consume your service, this ebook will guide you through the discovery process. Look at two major disruptions from the 1990s that businesses now take for granted Explore how successful businesses such as Uber created market niches by mixing several technologies in clever ways Learn eight ways to spot disruption opportunities, including underserved markets, sources of waste, and artificial barriers to entry Dive into detailed examples of disruption today: the cloud, predictive analytics and machine learning, multi-sided markets, and self-publishing.